Español - Guagalango Guambiango, Gladys; Gallegos Navas, Miriam (Revista Ecos de la Academia, 2021)
Sensory Integration (SI) constitutes the child’s ability to feel, understand and organize the sensory information coming from his body and his environment. This information is transmitted through the sensory systems (vision, touch, smell, taste and hearing), as well as through the vestibular and proprioceptive systems. The need arises then to analyze the experiences of application of Sensory Integration within the classroom to work with children with disabilities. In addition, identify the different applications of Sensory Integration, describe how it contributes to integral development and propose educational strategies to contribute to the management and strengthening of it in children with disabilities. The theoretical construction of this work is carried out through an investigation with a qualitative approach through the bibliographic or documentary review and subsequent analysis of the most relevant scientific articles and investigations and references of the central motive of this investigation, which finally lay the foundations and the theoretical foundation regarding the importance of promoting Sensory Integration for integral development, since the results of this research highlight that a correct application of sensory integration activities generates positive effects in activities of daily life, in school activities and in self-care of children with disabilities.